Analytics technology integration in sepak takraw training management to optimize athlete performance - Saparia, Andi; Sardiman, Sardiman; Saldi, Muh.; Muhammad Agusman; Usba, Muhamad (Tanjungpura Journal of Coaching Research, 2026)
Background Sepak takraw performance depends on technical skill and physical fitness. However, the use of analytics technology to support training management in community-based sepak takraw programs remains limited. Therefore, this study examined changes in athletes' technical and physical performance following the integration of analytics technology into training management. Objectives This study examined changes in the technical and physical performance of community-based sepak takraw athletes after analytics technology was incorporated into training management. Methods A one-group pretest-posttest study involved 24 active athletes from Puse Village, Tolitoli Regency, Central Sulawesi, Indonesia, recruited through total sampling. Over 12 weeks, four weekly training sessions integrated wearable monitoring, video-based technical analysis, and a digital performance database. Outcomes were service accuracy, smash effectiveness, Illinois Agility Test time, computerized reaction time, and athletes' perceptions of the system. Pre-post outcomes were evaluated with paired-samples tests at p < .05, while perception scores were summarized descriptively. Results Service accuracy increased from 68.42% to 82.17% (+20.10%, p < .001), and smash effectiveness increased from 71.36% to 84.91% (+18.98%, p < .001). Agility time decreased from 17.83 to 16.08 s (-9.80%, p = .002), and reaction time decreased from 342.16 to 303.15 ms (-11.40%, p = .001). Perception ratings were favorable, with the highest mean for training effectiveness (4.63) and an overall satisfaction mean of 4.48. Conclusion Technical and physical performance improved during the technology-supported program, and athletes evaluated the system positively. Analytics technology appears feasible for community-based sepak takraw training, but controlled studies with complete inferential statistics are needed before improvements can be attributed exclusively to the intervention.